Surgical Treatment of a Unique Dermatofibroma in a Lactating Holstein Cow: Histopathologic and Immunohistochemical Features - Mahan Sarebani; Soroush Sabiza; Annahita Rezaie; Abdolvahed Moarabi; Farid Shahbandari (Iranian Journal of Veterinary Surgery)
A lactating 6-year-old, black-white, Holstein cow, weighing about 300 kg, presented for a mass on her carp joint (right forelimb) with severe swelling of the entire carp. The cow had untreated swelling 3 months before. This mass was small initially, but it became larger and harder over time. It was decided to take a tissue sample through fine needle aspiration but this work was not successful because the mass was too hard. Plain radiography showed just abundant soft tissue swelling with no pathology in the carpal joint. Under local anesthesia, the entire mass was removed surgically. Dermatofibroma was diagnosed by histopathologic assessment. This report aimed to describe a unique carpal dermatofibroma in a cow.